Economics of gastrointestinal nematode parasite control: The case of protein supplementation - Haile, Aynalem; Baker, R.L.; Rege, J.E.O. (Ethiopian Society of Animal Production, 2002)
The economic and biological efficiency of cotton seed cake (CSC) and molasses urea block (MUB) supplementation to control gastrointestinal nematode parasites was examined in artificially infected Horro and Menz lambs from 3 to 12 months of age. The factorial O.xperimental design involved 2 breeds, 2 infection treatments (infected vs non-infected) and 3 dietary protein treatments (hay only, hay plus molasses urea blocks, hay plus cotton seed cake). Challenge with endoparasites involved three infection periods each separated by an anthelmintic treatment. Cost benefit analysis was carried out using partial budget. Protein supplementation of lambs with CSC and MUB resulted in lower levels of fecal egg counts (FEC) and higher packed cell volume (PM and growth rates than lambs that were fed the basal diet. This result suggests that protein supplementation would help lambs to with stand the pathogenic effects of parasites. In all the infection phases and for all nutritional treatments, non-infected lambs had better net return than their infected counterparts. This is a result of weight gain difference. In the first two infections, supplemented lambs (those kept on CSC) had slightly net return than lambs on the basal diet. However, this advangage was not maintained in the tertiary infection. In fact, control lambs were better than those on the supplemented diets during the tertiary, infection. Ethiopian Society of Animal Production. Thus, biological efficiency was not translated to economic efficiency in this study. Future studies should examine other cheaper protein sources. However this study concludes that parasite control strategies and economic analysis should go hand in hand.